What is qualitative interviewing? - Edwards, Rosalind; Holland, Janet (London : Bloomsbury, 2013)
This text makes clear the procedures and practices surrounding qualitative interviewing. Qualitative interviews are a critical part of qualitative research, but understandings of what it means to carry out interviews have shifted over time. It provides the latest studies and practical guidance on how to cater for a broad range of research. It shows researchers and students how to begin with key questions and theories and the best interviewing tactic to take.
Includes bibliographical references (pages 99-124) and index.
Keywords: Social sciences -- Research -- Methodology; Interviewing